A randomised controlled trial of a probiotic and a prebiotic examining metabolic and mental health outcomes in adults with pre-diabetes. Issue 3 (24th March 2022) - Barthow, Christine; Hood, Fiona; Crane, Julian; Huthwaite, Mark; Weatherall, Mark; Parry-Strong, Amber; Krebs, Jeremy
Abstract : Aims: To evaluate the effect of the probiotic Lactobacillus rhamnosus HN001 and/or cereal enriched with oat-derived beta-glucan (OBG) on metabolic and mental health outcomes when administered to adults with pre-diabetes. Design: 2×2 factorial design randomised, parallel-groups placebo-controlled; double-blinded for probiotic, single-blinded for cereals. Participants: Community-dwelling adults aged 18–80 years with pre-diabetes: glycated haemoglobin (HbA1c ) 41–49 mmol/mol. Interventions: Capsules containing Lactobacillus rhamnosus (HN001) (6×10 9 colony-forming units/day), or placebo capsules; and cereal containing 4 g/day OBG or calorie-matched control cereal, taken daily, for 6 months. Study groups were: (A) HN001 capsules+OBG cereal; (B) HN001 capsules+control cereal; (C) placebo capsules+OBG cereal and (D) placebo capsules+control cereal. Outcome measures: Primary outcome: HbA1c at 6 months. Secondary outcomes: fasting plasma glucose, fasting insulin, homeostatic model assessment of insulin resistance, fasting lipids, blood pressure, body weight, waist circumference, body mass index and mental well-being. Results: 153 participants were randomised. There was complete HbA1c outcome data available for 129 participants. At 6 months the mean (SD) HbA1c was 45.9 (4.4) mmol/mol, n = 66 for HN001, and 46.7 (4.3) mmol/mol, n = 63 for placebo capsules; 46.5 (4.0) mmol/mol, n = 67 for OBG and 46.0 (4.6) mmol/mol n = 62 for control cereal. The estimated difference between HN001-placebo capsules was −0.83, 95% CI −1.93 to 0.27 mmol/mol, p=0.63, and between OBG-control cereals −0.17, 95% CI −1.28 to 0.94 mmol/mol, p=0.76. There was no significant interaction between treatments p=0.79. There were no differences between groups or significant interactions between treatments for any of the secondary outcomes. Conclusions: This study found no evidence of clinical benefit from the supplementation with either HN001 and/or cereal containing 4 g OBG on HbA1c and all secondary outcomes relevant to adults with pre-diabetes. Trial registration number: Australian New Zealand Clincial Trials Registry number ACTRN12617000990325